Free perivascular tissue flap transfer. Issue 7 (July 2015) - Matsuda, Ken; Kubo, Tateki; Fukai, Megumi; Kikuchi, Mamoru; Hikasa, Hisashi; Nakajima, Yoriko; Tomita, Koichi; Shibata, Minoru; Hosokawa, Ko
Summary Local flaps and composite grafting are the procedures of choice for reconstructing relatively small soft tissue defects. However, despite their limited conveyable volume, local flaps sometimes require a wide dissection area and long new incisions. Composite grafts also have serious limitations and require a well-vascularized recipient bed. To overcome these limitations, we used a free vascularized perivascular tissue flap based on the descending branch of the lateral femoral circumflex artery. Using this method, we performed reconstructions for seven patients (four cases in head and neck region and three cases in lower limb) with various soft tissue defects (ranged from 4.0 cm3 to 40.0 cm3). This flap was easily elevated, without the need for precise preoperative flap design, and the flap volume was adjustable regardless of whether deep fascia and muscle were included. The flap has a rich vascular supply, which allows bone and cartilage tissue to be combined with the transfer of soft tissue, and satisfactorily treats chronic wounds with poor blood supply.